Frequency of Inflammatory Diarrhoea (Faecal Leukocyte Count ≥ 5/Ml Or Faecal Cal-protetctin Positive) in young patients presenting with Acute Gastroenteritis - Syed Anees A. Gardezi, Najmusaqib K. Niazi, Syed Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Muneeb Ur Rehman, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
One of the common dilemma and the most important cause of child death below the age of 5 years in developing countries is acute gastroenteritis. Aim: To check the frequency of inflammatory diarrhoea (faecal leukocyte count ≥ 5/ml or faecal calprotetctin positive) in young patients presenting with acute gastroenteritis in hospital. Study design: Descriptive cross sectional study. Methodology: Patients (n=366) within the age range of 1 day to 6 years presenting to the OPD with the complaints of symptoms associated with acute gastroenteritis (diarrhoea with or without abdominal pain, vomiting and nausea) were included into the study. Patients demographic data were collected. Stool samples from the patients were obtained in sterile bottles and sent for Stool RE and CS examination. All this information was recorded on Performa. Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: Out of total 366 patients 178 (48.6%) were male and 188(51.4%) were female. Mean age of the patients presenting to the OPD/MRC was 826 days (2.2 years) ± 618 days, with a range 13 days to 2187 days (5.9 years). Frequency of inflammatory diarrhea was 193(52.7%) among patients presenting with acute gastroenteritis as compared to non inflammatory diarrhoea. Conclusion: It was concluded that frequency of inflammatory diarrhoea in young patients presenting with acute gastroenteritis is alarmingly high in our region. Various programs for the identification and eradication of causative factors and organisms should be carried out along with education of masses about this fatal condition.